Microstructural evolution at Cu/Sn-Ag-Cu/Cu and Cu/Sn-Ag-Cu/Ni-Au ball grid array interfaces during thermal ageing - Marques, V; Johnston, C; Grant, P (Elsevier, 2014)
The effect of metallization chemistry on the solid state growth kinetics of intermetallics formed in an industrial metallization/solder/metallization arrangement during isothermal ageing has been studied. During isothermal ageing of the Cu/Sn-Ag-Cu/Cu arrangement at temperatures lower than 125 °C, Cu was the main mobile element and diffused either through or along interfacial Cu 6Sn5 grain boundaries to react with Sn on the solder side of the Cu6Sn5 layer; while for temperatures greater than 125 °C, both Cu and Sn were relatively mobile. Isothermal ageing of the Cu/Sn-Ag-Cu/Ni-Au asymmetric arrangement showed a concentration gradient of Ni and Cu across the entire ball in the solder joints leading to an inhomogeneous precipitation of (Cu, Ni)6Sn5 in the vicinity of the Ni metallization. Ni alloying of the interface reaction products also occurred in the vicinity of the Cu metallization, reducing the growth rate of Cu 6Sn5 and Cu3Sn by 20% and 70% respectively when compared with symmetric Cu/Sn-Ag-Cu/Cu arrangement. Growth rate studies and microscopy suggested the presence of the Cu6Sn5 η' → η transformation during extended ageing in the region of 150-175 °C, which is generally under-reported in these important commercial systems. © 2014 Elsevier B.V. All rights reserved.